2014
DOI: 10.1007/s00432-014-1877-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of monocarboxylate transporter genes are associated with clinical outcomes in patients with colorectal cancer

Abstract: Our findings suggest that SNPs in MCT1 and MCT2 genes may affect clinical outcomes and can be used to predict the response to adjuvant chemotherapy in CRC patients who received surgical treatment once validated in future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…One of the recently recognized hallmarks of cancer is altered glucose metabolism with dependence on glycolysis for energy production [ 4 ]. Consequently, large amounts of lactate produced have to be exported to the extracellular milieu; thus, it is not surprising that cancer cells exhibit high levels of MCT expression to maintain this metabolic phenotype [ 9 , 10 ]. In this context, MCT1 and MCT4 on one hand play a dual role in the maintenance of high glycolytic rates by performing lactate efflux, and on the other hand contribute to the homeostasis of the intracellular pH through the cotransport of protons [ 81 ].…”
Section: Mcts In Tumorsmentioning
confidence: 99%
“…One of the recently recognized hallmarks of cancer is altered glucose metabolism with dependence on glycolysis for energy production [ 4 ]. Consequently, large amounts of lactate produced have to be exported to the extracellular milieu; thus, it is not surprising that cancer cells exhibit high levels of MCT expression to maintain this metabolic phenotype [ 9 , 10 ]. In this context, MCT1 and MCT4 on one hand play a dual role in the maintenance of high glycolytic rates by performing lactate efflux, and on the other hand contribute to the homeostasis of the intracellular pH through the cotransport of protons [ 81 ].…”
Section: Mcts In Tumorsmentioning
confidence: 99%
“…SLC16A1 rs1049434 (in near-perfect LD with rs7169 and rs7556664) was studied the most due to its exonic location, and the fact that it affects MCT1 protein structure [ 22 , 23 , 24 , 25 ]. It has been shown that the mutated variant (containing Glu in the protein sequence and T in the DNA sequence) exhibits increased lactate transport via SLA16A1, as compared to the wild type Asp/A [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, induction of MCT1 expression has been observed with GHB and butyrate exposure (46,47) indicating that chronic exposure to MCT substrates may lead to increased expression levels. Few studies are available assessing the impact of polymorphic variants of MCTs/SMCTs on transporter function; recent studies have identified potential functional MCT polymorphisms that influence plasma lactate accumulation (48) and prognosis in colorectal cancer (49). Future studies should assess the impact of altered MCT expression on the distribution and toxicokinetics of GHB.…”
Section: Discussionmentioning
confidence: 99%